2023
DOI: 10.1094/pdis-09-22-2125-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Leaf Spot and Stem Blight on Blueberry (Vaccinium corymbosum ‘Bluerain’) Caused by Calonectria pseudoreteaudii in China

Abstract: Blueberry has high nutritional value and is one of the five healthy fruits. In 2018, leaf spots and stem blights were observed on Vaccinium corymbosum cv. Bluerain in Guangzhou, Guangdong Province, China. Up to 80% of the plants were affected. Initial symptoms of affected leaves were red-brown, irregular, small spots, which gradually coalesced and formed larger irregular necrotic patches. The affected stems showed red-brown and irregular large lesions. Diseased tissues were surface sterilized with 75% alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Anthracnose fungi are ubiquitous pathogens in nature and represent significant phytopathogens of numerous economic crops, including Fragaria × ananassa Duch [55], Vitis vinifera L. [56], Malus pumila Mill [57], Mangifera indica L. [58], etc., resulting in negative impacts on plant growth and reduced yields, leading to substantial economic losses. Blueberry anthracnose is a significant disease in many countries, causing damage to blueberry production throughout the year by affecting leaves, branches, and fruits [14,31,59]. In previous reports, C. gloeosporioides and C. acutatum were confirmed as the main pathogens [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthracnose fungi are ubiquitous pathogens in nature and represent significant phytopathogens of numerous economic crops, including Fragaria × ananassa Duch [55], Vitis vinifera L. [56], Malus pumila Mill [57], Mangifera indica L. [58], etc., resulting in negative impacts on plant growth and reduced yields, leading to substantial economic losses. Blueberry anthracnose is a significant disease in many countries, causing damage to blueberry production throughout the year by affecting leaves, branches, and fruits [14,31,59]. In previous reports, C. gloeosporioides and C. acutatum were confirmed as the main pathogens [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Examples include stem blight caused by Neofusicoccum vaccinii [8], anthracnose caused by Colletotrichum acutatum and C. gloeosporioides [9,10], anthrax caused by Pestalotiopsis spp. [11], Nigrospora oryzae [12], Diaporthe phoenicicola [13], and leaf spot disease caused by Calonectria pseudoreteaudii [14]. The diseases have resulted in significant economic losses to the blueberry industry.…”
Section: Introductionmentioning
confidence: 99%
“…sp. in China and Laos [ 59 , 60 ] and caused leaf spot and stem blight in Vaccinium corymbosum L. in China [ 61 ]. The results of this and previous studies suggested that C. pseudoreteaudii is an important pathogen in many plant species with a wide geographic distribution.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Eucalyptus in China, C. pseudoreteaudii has been isolated from Eucalyptus hybrids in Vietnam, India, and Indonesia; Macadamia sp. in Vietnam, Lao, and China; and blueberry in China [13,[15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%